2018
DOI: 10.1017/s1047951117002372
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and neonatal micronutrient levels in newborns with CHD

Abstract: We thought that high homocysteine and zinc levels and low vitamin D levels in mother-infant pairs might have a role in the aetiopathogenesis of CHD. Large-scale, prospective studies are needed to clarify the role of micronutrients in CHDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(32 citation statements)
references
References 35 publications
(47 reference statements)
1
22
0
Order By: Relevance
“…Few studies were conducted to investigate the association between maternal vitamin D level and risk of CHD in offspring. Similar to our results, Dilli et al 32 conducted a case control study to measure serum level of micronutrients (including vitamin D) in 108 neonates with CHD and their mothers. They found a significant decrease in vitamin D level in both neonates and their mothers compared to controls.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Few studies were conducted to investigate the association between maternal vitamin D level and risk of CHD in offspring. Similar to our results, Dilli et al 32 conducted a case control study to measure serum level of micronutrients (including vitamin D) in 108 neonates with CHD and their mothers. They found a significant decrease in vitamin D level in both neonates and their mothers compared to controls.…”
Section: Discussionsupporting
confidence: 86%
“…Few studies reported association between vitamin D level and specific CHD phenotype. Despite the difference in CHD phenotype classification, Dilli et al 32 found that maternal and neonatal vitamin D level were lower in truncal anomalies including truncus arteriosus, tetralogy of Fallot, and D-transposition of great arteries. In addition, Koster et al 33 reported that there was a significant association between maternal vitamin D status (deficient and moderate) and isolated group of congenital heart disease but not a complex one.…”
Section: Discussionmentioning
confidence: 99%
“…In one study in Germany, maternal serum vitamin B 12 and holotranscobalamin (holoTC) concentrations at delivery were significantly correlated with cord blood holoTC concentrations ( p < 0.05) [18]. In contrast, findings from cross-sectional studies examining the associations between maternal and infant vitamin B 12 concentrations later in the postpartum period have been heterogeneous [35,36,37,38,39,40]. Maternal vitamin B 12 and holoTC concentrations were significantly correlated with infant vitamin B 12 concentrations in the first month (i.e., 2–30 days) postpartum in a study in Turkey [38].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this case-control study was carried out with the standardized time determined as after neonatal birth. Dilli et al reported that serum vitamin D levels in both mothers and neonates were relatively low, indicating that these ratios were effective in the pathogenesis of CHD (30).…”
Section: Discussionmentioning
confidence: 99%